PHF20 is crucial for epigenetic control of starvation-induced autophagy through enhancer activation - Park, Se Won; Kim, Jaehoon; Oh, Sungryong; Lee, Jeongyoon; Cha, Joowon; Lee, Hyun Sik; Kim, Keun Il; Park, Daechan; Baek, Sung Hee (Nucleic Acids Research, 2022)
Autophagy is a catabolic pathway that maintains cellular homeostasis under various stress conditions, including conditions of nutrient deprivation. To elevate autophagic flux to a sufficient level under stress conditions, transcriptional activation of autophagy genes occurs to replenish autophagy components. Thus, the transcriptional and epigenetic control of the genes regulating autophagy is essential for cellular homeostasis. Here, we applied integrated transcriptomic and epigenomic profiling to reveal the roles of plant homeodomain finger protein 20 (PHF20), which is an epigenetic reader possessing methyl binding activity, in controlling the expression of autophagy genes. Phf20 deficiency led to impaired autophagic flux and autophagy gene expression under glucose starvation. Interestingly, the genome-wide characterization of chromatin states by Assay for Transposase-Accessible Chromatin (ATAC)-sequencing revealed that the PHF20-dependent chromatin remodelling occurs in enhancers that are co-occupied by dimethylated lysine 36 on histone H3 (H3K36me2). Importantly, the recognition of H3K36me2 by PHF20 was found to be highly correlated with increased levels of H3K4me1/2 at the enhancer regions. Collectively, these results indicate that PHF20 regulates autophagy genes through enhancer activation via H3K36me2 recognition as an epigenetic reader. Our findings emphasize the importance of nuclear events in the regulation of autophagy.
Keywords: Autophagy; Chromatin; DNA-Binding Proteins; Epigenesis, Genetic; Epigenomics; Homeodomain Proteins; Humans; Starvation; Transcription Factors